Rethinking securities law - Steinberg, Marc I. (New York, NY : Oxford University Press, 2021)
In 1978, the American Law Institute (ALI) adopted the ALI Federal Securities Code. The Code has not been enacted by Congress and its prospects are dim. The objective of this book is to identify the deficiencies that exist under the current regimen, address their failings, provide recommendations for rectifying these deficiencies, and set forth a thorough analysis for remediation to prescribe a consistent and sound securities law framework.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 30, 2021).
Keywords: Securities -- United States